2020
DOI: 10.3389/fped.2020.00426
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic vs. Open Pyloromyotomy in Treatment of Infantile Hypertrophic Pyloric Stenosis

Abstract: Background/Purpose: Laparoscopic pyloromyotomy gained wide popularity in management of pyloric stenosis with contradictory results regarding its benefits over classic open approach. This study aimed at comparing both regarding their safety, efficiency, and outcome. Methods: This is a prospective randomized controlled study performed from April 2017 to April 2019. It included 80 patients, divided randomly into two groups, where laparoscopic pyloromyotomy was performed in group A and open pyloromyotomy in group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 25 publications
2
9
0
7
Order By: Relevance
“…In contrast to previous reports, Zampieri et al in their study in 60 infants did not find statistically significant difference in regards to outcomes of treatment and complication rates between two operative techniques and concluded that laparoscopic approach is a comparable alternative to the open approach [29]. Similar conclusion was drawn by Shawn et al who reported, among 200 infants, only lesser pain after the procedure and fewer complication rates in the laparoscopic group [30].…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…In contrast to previous reports, Zampieri et al in their study in 60 infants did not find statistically significant difference in regards to outcomes of treatment and complication rates between two operative techniques and concluded that laparoscopic approach is a comparable alternative to the open approach [29]. Similar conclusion was drawn by Shawn et al who reported, among 200 infants, only lesser pain after the procedure and fewer complication rates in the laparoscopic group [30].…”
Section: Discussionmentioning
confidence: 50%
“…Last two to three decades laparoscopic surgery gained popularity among pediatric surgeons, especially after development of instruments suitable for the pediatric population. Various pediatric procedures such as hernia repair, varicocelectomy, cholecystectomy, appendectomy, pyloromyotomy etc., which until then had been performed exclusively by the open approach, began to be performed using laparoscopic approach [15][16][17][18][19][20][21][25][26][27][28][29]. Numerous studies reported benefits of laparoscopic approach for treatment of hypertrophic pyloric stenosis such as faster recovery, faster postoperative feeding, lesser pain, shorter surgical and hospitalization times and lower incidence of wound related complications [6,11,[15][16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35], протягом багатьох десятиліть залишалась основним методом лікування дітей із ГПС завдяки відмінним результатам і незначній кількості ускладнень [7,20]. У 1991 р. J. L. Alain зі співавторами вперше повідомили про ла-пароскопічну пілороміотомію [2], яка поступово почала широко застосовуватися в щоденній практиці дитячих хірургів [10,22,24].…”
Section: śžŝđğ žĩ ŵğƚśžě žĩ ƚśğ ƚƌğăƚŵğŷƚ ŝŷ ŷğǁďžƌŷɛ ǁŝƚś śljɖğƌƚƌžɖś...unclassified
“…Відкрита пілороміотомія залишається основним методом хірургічного втручання і дітей із ГПС, незва- Тривалість лапароскопічної пілороміотомії була довшою порівняно з традиційною, проте ця різниця не є статистично достовірною (р=0,124), що відповідає даним літератури [37,46], хоча в інших дослідженнях тривалість лапароскопічного втручання менша [24,34]. Слід зазначити, що зі збільшенням досвіду тривалість лапароскопічної пілороміотомії скорочується, на чому наголошують й інші дослідники [5].…”
Section: результати дослідження та їх обговоренняunclassified